Activation of PPG neurons following acute stressors differentially involves hindbrain serotonin in male rats. (1st April 2021) - Leon, Rosa M.; Borner, Tito; Stein, Lauren M.; Urrutia, Norma A.; De Jonghe, Bart C.; Schmidt, Heath D.; Hayes, Matthew R.
Abstract: Within the hindbrain, serotonin (5-HT) functions as a modulator of the central glucagon-like peptide-1 (GLP-1) system. This interaction between 5-HT and GLP-1 is achieved via 5-HT2C and 5-HT3 receptors and is relevant for GLP-1-mediated feeding behavior. The central GLP-1 system is activated by various stressors, activates the hypothalamic pituitary adrenocortical (HPA) axis, and contributes to stress-related behaviors. Whether 5-HT modulates GLP-1's role in the stress response in unknown. We hypothesized that the serotonergic modulation of GLP-1-producing neurons (i.e., PPG neurons) is stimuli-specific and that stressed-induced PPG activity is one of the modalities in which 5-HT plays a role. In this study, we investigated the roles of 5-HT2C and 5-HT3 receptors in mediating the activation of PPG neurons in the nucleus tractus solitarius (NTS) following exposure to three different acute stressors: lithium chloride (LiCl), noncontingent cocaine (Coc), and novel restraint stress (RES). Results showed that increased c-Fos expression in PPG neurons following LiCl and RES—but not Coc—is dependent on hindbrain 5-HT2C and 5-HT3 receptor signaling. Additionally, stressors that depend on 5-HT signaling to activate PPG neurons (i.e., LiCl and RES) increased c-Fos expression in 5-HT-expressing neurons within the caudal raphe (CR), specifically in the raphe magnus (RMg). Finally, we showed that RMg neurons innervate NTS PPG neurons and that some of these PPG neurons lie in close proximity to 5-HT axons, suggesting RMg 5-HT-expressing neurons are the source of 5-HT input responsible for engaging NTS PPG neurons. Together, these findings identify a direct RMg to NTS pathway responsible for the modulatory effect of 5-HT on the central GLP-1 system—specifically via activation of 5-HT2C and 5-HT3 receptors—in the facilitation of acute stress responses. Highlights: Hindbrain 5HT2C and 5HT3 receptors mediate activity of PPG neurons in response to lithium chloride and novel restraint. LiCl and novel restraint activate 5-HT neurons in the Raphe Magnus (RMg). RMg neurons monosynaptically innervate NTS PPG neurons.